"An Analysis of Consumer Purchase Patterns and Attitudes Toward Organic Foods and Goods" (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
"This research study aims to understand consumer purchasing behavior and perceptions regarding organic foods and products, as well as the public's awareness of organic products, their evolving trends, and technologies. While metro cities have been hubs for organic products, their presence is now noticeable in smaller towns. Therefore, the respondent group comprises consumers of various ages and professions from different states across the country, with conclusions drawn based on the researcher's interpretation of consumer responses. The sample for data collection was selected based on the researcher's convenience, aligning with the study's purpose. The current study sheds light on various factors related to consumer behavior, perceptions, and awareness. To better understand consumer perceptions of organic products, various literature sources were reviewed, and data were collected from primary and secondary sources. A survey was conducted using a self-administered questionnaire distributed online via Google Forms. The collected data were tabulated and analyzed through graphs and charts. A hypothesis was stated for this research, and its significance was tested using the t-Test. The study observes that individuals across all age groups are not fully aware of organic products, and factors such as price, safety, and environmental protection influence consumer behavior. Hence, it concludes that the organic food industry needs to enhance public awareness."